Effect of Goat and Cow Manure Fertilizer on the Growth of Shallot (Allium ascalonicum L) - I Made Dharma Atmaja; A. A. Ngurah Mayun Wirajaya; Luh Kartini (Warmadewa University Press, 2019)
The purpose of this research is to find out the effect of the distribution of goat and cow manure on the growth and yield of shallots (Allium ascalonicum L.). The study was conducted from 28 October to 13 December 2016. This study used a randomized block design (RBD) with 2 factors consisting of 4 levels of treatment, each treatment was repeated 3 times so that 16 treatment combinations were obtained. In this experiment, 48 trial plots are needed. The results showed that in the distribution of goat manure the highest fresh tuber weight was obtained from a dose of 30 tons / ha (K3) which was 7.35 g and the oven dry weight of the tuber was obtained from administering a dose of 10 tons / ha (K1) which was 1.78 gram. Meanwhile, fresh weight and dry weight of tubers in the administration of cow manure tend to be obtained at the administration of a dose of 30 tons / ha which have values of 7.27 g and 1.65 g, respectively.